Designing the Macrocyclic Dimension in Main Group Chemistry. Issue 13 (4th January 2018) - Niu, Hao‐Che; Plajer, Alex J.; Garcia‐Rodriguez, Raul; Singh, Sanjay; Wright, Dominic S.
Abstract: Outside the confines and well‐established domain of organic chemistry, the systematic building of large macromolecular arrangements based on non‐carbon elements represents a significant and exciting challenge. Our aim in the past two decades has been to develop robust synthetic methods to construct new types of main group architectures in a methodical way, principles of design that parallel those used in the organic arena. This Concept article addresses the fundamental thermodynamic and kinetic problems involved in the design and synthesis of main group macrocycles and looks to future developments of macromolecules in this area, as well as new applications in coordination chemistry. Abstract : Circling the Square : Developing systematic strategies to inorganic macrocycles, which parallel the type of design principles used for organic counterparts, is a major challenge. A simple approach involving combination of dimeric (electrophilic and nucleophilic) P2 N2 ring components has proved to be remarkably selective in building macrocyclic phosphazanes, uncovering the potential for new host–guest chemistry in this area.